Challenges in Collaborative Comic Strip Writing and Publishing: University Students’ Experiences and Strategies - Erawati Paramita, Paulina (UNIVERSITAS SERAMBI MEKKAH, 2024)
The integration of creative arts into academic curricula has gained recognition for its potential to enhance student engagement, collaboration, and critical thinking. One innovative approach is collaborative comic strip writing and publishing, which merges visual storytelling with written expression. Despite its benefits, students often encounter challenges in the process, including language-related difficulties, group dynamics, and visual representation issues. This qualitative study explores the experiences of 20 university students engaged in a collaborative comic strip project as part of a Basic Writing course. Using a phenomenological approach, data were collected through semi-structured interviews and focus group discussions. Findings reveal that students faced significant obstacles related to vocabulary limitations, maintaining logical flow, negotiating creative differences, and technical constraints in digital publishing. To address these challenges, students employed strategies such as utilizing online writing tools, structured brainstorming sessions, peer feedback, role assignments, and digital design platforms. The study highlights the value of integrating digital tools and structured collaboration techniques to enhance the effectiveness of comic strip writing in educational settings. These insights offer practical recommendations for educators seeking to incorporate visual storytelling into their teaching methodologies.